2016
DOI: 10.1063/1.4949272
|View full text |Cite
|
Sign up to set email alerts
|

Nano-metrology: The art of measuring X-ray mirrors with slope errors <100 nrad

Abstract: We present a comprehensive investigation of the systematic and random errors of the nano-metrology instruments used to characterize synchrotron X-ray optics at Diamond Light Source. With experimental skill and careful analysis, we show that these instruments used in combination are capable of measuring state-of-the-art X-ray mirrors. Examples are provided of how Diamond metrology data have helped to achieve slope errors of <100 nrad for optical systems installed on synchrotron beamlines, including: iterative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…An additional pair (M5b) was implemented for the high-energy range (2-3 keV). The mechanics were designed so that each of the vertical stack of mirrors could be clamped separately and any induced clamping distortions could be checked on the Diamond-NOM before installation (Alcock et al, 2010(Alcock et al, , 2016. Each vertical stack of mirrors could then be installed into the main mechanics using three bolts from the back, minimizing the risk of any damage to the optical surfaces during installation.…”
Section: The M5 Mirror Systemmentioning
confidence: 99%
“…An additional pair (M5b) was implemented for the high-energy range (2-3 keV). The mechanics were designed so that each of the vertical stack of mirrors could be clamped separately and any induced clamping distortions could be checked on the Diamond-NOM before installation (Alcock et al, 2010(Alcock et al, , 2016. Each vertical stack of mirrors could then be installed into the main mechanics using three bolts from the back, minimizing the risk of any damage to the optical surfaces during installation.…”
Section: The M5 Mirror Systemmentioning
confidence: 99%
“…This environmentally stabilized laboratory contains a suite of metrology instruments capable of characterizing state-of-the-art synchrotron X-ray optics (Alcock et al, 2016). After assembly, each mirror was sequentially installed, aligned and tested on the Diamond-NOM (see Fig.…”
Section: Mechanical Bendermentioning
confidence: 99%
“…With such precautions, previous experiments have shown that the Diamond-NOM is capable of reliably measuring X-ray mirrors with slope errors < 50 nrad r.m.s. (Alcock et al, 2016). Bending motors were driven using a MCS8+ motion controller, via the Experimental Physics and Industrial Control System (EPICS), which enabled synchronization with Diamond-NOM scans also controlled via EPICS.…”
Section: Mechanical Bendermentioning
confidence: 99%
“…Pencil-beam devices, such as the long trace profiler (LTP), nanometer optical metrology (NOM), and their successive versions 11 17 , are widely used, simple to interpret, and able to measure X-ray mirrors up to 1.5 m long, but only along one dimension (1D) at a time. Each successive version has brought improved precision to the figure measurements, so that today’s NOM can inspect the figure of flat or weakly curved mirrors with remarkable precision: down to 50 nrad 18 20 . Nonetheless, despite the use of a penta-prism to keep the beam deflection independent of the slide’s pitch error, the sawtooth deviation (over 250 nrad rms) from the electronic autocollimator (AC) interferes with the NOM’s measurement of the angle of deflection of the surface under test, and special calibration should be used to minimize the sawtooth error 21 .…”
Section: Introductionmentioning
confidence: 99%